Effect of Health Education Based on the Protection Motivation Theory on Malaria Preventive Behaviors in Rural Households of Kerman, Iran - Ghahremani, Leila (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Malaria is one of the most serious diseases in pregnant women as well as children less than 5 years around the world. The present study aimed to investigate the effect of health education based on the protection motivation theory on malaria preventive behaviors in the households of Ghale Ganj, Kerman, Iran in 2011. METHODS: The present quasi-experimental study was conducted on 144 households covered by 8 health centers of Ghale Ganj, Kerman. The study samples were selected through systematic random sampling and the study data were collected using a questionnaire including demographic information, the constructs of the protection motivation theory, and a checklist for assessing the malaria preventive behaviors. After the pre-test, the intervention group underwent an educational intervention and after two months, the post-test was performed through the same questionnaire. Then, the data were entered into the SPSS statistical software (v. 18) and analyzed using Chi-square and Wilcoxon non-parametric tests. Besides, P < 0.05 was considered as statistically significant. RESULTS: Before the intervention, no significant difference was found between the two study groups regarding perceived vulnerability, perceived severity, response costs, self-efficacy, response efficacy, and malaria preventive behaviors. After the intervention, however, a significant increase was observed in the intervention group's mean scores of all the constructs of the protection motivation theory as well as malaria preventive behaviors (P < 0.01). CONCLUSIONS: According to the findings of the study, educational intervention based on the protection motivation theory is highly effective in promoting malaria preventive behaviors.